PENGARUH HAMBATAN SAMPING TERHADAP VOLUME LALU LINTAS DENGAN MENGGUNAKAN REGRESI LINIER BERGANDA (Studi Kasus: Ruas Jalan Ryacudu Kota Bandar Lampung) - Chandra Alip Pratama; Andantino Putra Palsamu; Estu Emma Apriliana (JURNAL ILMIAH PENELITIAN MAHASISWA, 2026)
Lampung is the southernmost province on the island of Sumatra and serves as the gateway to land and sea transportation from Sumatra to Java. Its provincial capital, Bandar Lampung, as the center of the city is not free from congestion problems. Ryacudu Road is one of the densest roads in Bandar Lampung City, particularly in the Sukarame sub-district connecting the Way Halim Fly Over and the Ryacudu Canal Road. Points of congestion occur along this road, namely illegal parking on the right and left sides of the road caused by side friction. As side friction increases, this study aims to examine how much side friction influences the traffic volume on Ryacudu Road, under the title "The Effect of Side Obstacles on Traffic Volume Using Multiple Linear Regression (Case Study: Ryacudu Road Section, Bandar Lampung City)". Field observations were carried out for two days, one holiday and one busy day (Monday 13 May 2019 and Saturday 18 May 2019), during peak hours 06.00 - 18.00 WIB. The data were analyzed using MKJI 1997 and Microsoft Excel. The results show that the highest traffic volume was 544.6 pcu/hour at 12.00-13.00 WIB on Saturday 18 May 2019, while the highest side friction was 224 pcu/hour at 14.00-15.00 WIB on Monday 13 May 2019, of the vehicle entering/exiting type, classified as high (H). From the regression modeling, a positive model was obtained on Saturday, with the highest value on the regression equation between entering/exiting vehicles and slow vehicles against traffic volume, namely 62.8%. Y = a + b3X3 + b4X4 = 25.053 + 2.566X3 + 8.198X4 With the coefficient of determination (R2) of 0.621